Bioactive small molecules produced by the human gut microbiome modulate Vibrio cholerae sessile and planktonic lifestyles. (1st January 2021) - Pauer, Heidi; Teixeira, Felipe Lopes; Robinson, Avery V.; Parente, Thiago E.; De Melo, Marília A. F.; Lobo, Leandro A.; Domingues, Regina M. C. P.; Allen-Vercoe, Emma; Ferreira, Rosana B. R.; Antunes, Luis Caetano M.
ABSTRACT: Humans live in symbiosis with a diverse community of microorganisms, which has evolved to carry out many specific tasks that benefit the host, including protection against invading pathogens. Within the chemical diversity of the gastrointestinal tract, small molecules likely constitute chemical cues for the communication between the microbiota and pathogens. Therefore, we sought to investigate if molecules produced by the human gut microbiota show biological activity against the human pathogen Vibrio cholerae . To probe the effects of the gut metabolome on V. cholerae, we investigated its response to small-molecule extracts from human feces, from a complex bacterial community cultivated in vitro, and from culture supernatants of Enterocloster citroniae, Bacteroides thetaiotaomicron, and Bacteroides vulgatus . Using RNA sequencing, we determined the impact of the human gut metabolome on V. cholerae global gene expression. Among the genes downregulated in the presence of the fecal extract, the most overrepresented functional category was cell motility, which accounted for 39% of repressed genes. Repression of V. cholerae motility by the fecal extract was confirmed phenotypically, and E. citroniae extracts reproduced this phenotype. A complex in vitro microbial community led to increased motility, as did extracts from B. vulgatus, a species present in this community. Accordingly, mucin penetration was also repressed by fecal and E. citroniae extracts, suggesting that the phenotypes observed may have implications for host colonization. Together with previous studies, this work shows that small molecules from the gut metabolome may have a widespread, significant impact on microbe–microbe interactions established in the gut environment.